Βιβλιοκρισία:S. PAPAIOANNOU, Michael Psellos: Rhetoric and Authorship in Byzantium, Cambridge: Cambridge Univ. Press, 2013. ISBN 978-1-107-02622-3 - ΑΝΤΩΝΟΠΟΥΛΟΥ, Θεοδώρα (Byzantina Symmeikta, 2016)
Βιβλιοκρισία: S. Papaioannou, Michael Psellos: Rhetoric and Authorship in Byzantium, Cambridge: Cambridge Univ. Press, 2013. ISBN 978-1-107-02622-3